Effect of music as a therapeutic resource in a support group for the elderly - Joycimara da Silva Sales de Medeiros; Luciane Paula Batista Araújo de Oliveira; Anna Cecília Queiroz de Medeiros; Rafaela Carolini de Oliveira Távora; Wanessa Cristina Tomaz dos Santos Barros (Rev Rene)
Objective: to analyze the effect of musical interventions to reduce stress levels in the elderly. Methods: quantitative research, of quasi-experimental type, in which the level of stress was assessed before and after interventions with the music therapy method, called receptive experience, in 25 elderly people in a support group. The Perceived Stress Scale was used and descriptive and inferential statistical analysis was performed. Results: in the assessment of perceived stress, the average was 33.6 (standard deviation 5.17) points in the pre-test and 31.6 (standard deviation 2.29) points in the post-test (p<0.05). In the assessment dimension, the reduction was identified only in the perceived distress factor. Pre-tests outcomes showed that the higher the monthly income, the lower the perceived stress (p=0.043). Conclusion: musical interventions with the participants of this study were able to reduce stress levels, indicating the importance of music as a therapeutic resource in health promotion actions.